Adjusting to bilateral trade liberalisation under an EPA: Evidence for Mauritius - Chris Milner; Oliver Morrissey; Evious Zgovu (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2007)
This paper estimates the impact and adjustment costs for Mauritius of eliminating tariffs on imports from the EU under an EPA, considering trade, revenue, welfare, production and employment effects, and considering the potential benefit of preserving preferential access to the EU market. Assuming `immediate' complete elimination of all tariffs on imports from the EU, there is a small welfare loss (-0.17% of 2002 GDP) unless we include potential production gains (generating a welfare gain of 0.06% of GDP). Excluding up to 20% of imports as sensitive products, the overall welfare loss is -0.19% of GDP. However, potential adjustment costs are much greater than these low welfare effects suggest: tariff revenue will fall by 33-52% of 2002 levels, domestic (non-export) production will decline by almost a quarter and direct employment by 12% (about 11,000 jobs lost overall). Preferences under an EPA are unlikely to support any growth in the major export sectors (sugar and garments), so absorbing the adjustment costs will be difficult.
Keywords: F14; F15; F17; 330; EU-ACP; Economic Partnership Agreements; Mauritius; Außenhandelsliberalisierung; Handelsabkommen; Wirkungsanalyse; Mauritius; EU-Staaten